THE EFFECT OF THREE PHASE TECHNIQUE ON STUDENTSâ€™ READING COMPREHENSION - Nurdiansa, Eko Saputra (Journal of Teaching of English, 2019)
The objective of the study is to know whether or not three phase techniqueÂ  Â hasÂ Â  significantÂ  Â effectÂ  Â onÂ  Â studentsâ€™ reading comprehension. The design of this study was quasi experimental research. The population of the study were students who were taking Reading 1 class in English study program at Halu Oleo University in academic year of Â 2016-2017.Â  By Â employing Â purposive Â sampling technique the researcher chose class A as the sample of this study. Instrument of study was reading comprehension test in form of multiple choices questions. The result of this study confirmed that the teaching reading Â by Â using Â three Â phase Â reading Â techniqueÂ  could give significant effect on the studentsâ€™ reading comprehension. Based on the Paired Sample Test, it was found that there was a significant difference of studentsâ€™ reading comprehension score before and after they were given treatment by using three phase reading technique procedure in Reading 1 class with the significant degree of 0.013. Furthermore, there was also significant improvement in students' mean score (79.78). Therefore, the proposed hypothesis which stated â€œthree phase reading technique has significant effect on studentsâ€™ reading comprehensionâ€ was accepted.Â Keywords:Â Three Phase Technique,Â Reading Comprehension